FORnanoSatellites - Innovations in Nano-satellites - A Bavarian Research Alliance - Fey, Dietmar; Schilling, K.; Franke, Jörg; Schmidt, M.; Fuchs, C. (Lecture Notes in Computer Science, 2026)
The research alliance “FORnanoSatellites - Innovations in nano-satellites - Advanced assembly and mounting technology (AMT), packaging, computing technology, and applications”, funded by the Bavarian Research Foundation, pursues the design a new generation of nano-satellites, which have a spatial dimension of a few dm3 and mass of only a few kilograms. In the ‘New Space’ sector, nano-satellites are already opening up a wide range of applications in telecommunications, earth observation, and navigation in a cost-effective manner, e.g. in multisatellite networks. Standardization approaches are intended to support a cost-efficient production of hundreds of satellites. FORnanoSatellites intends to carry out research work to boost the development of small-scale production of nano-satellites in the long term. Open research challenges are in (i) the area of computer architecture for processing data. Furthermore, for the success of this technology (ii) a new mounting and interconnection 3D stacking technology of all components is required and a web configurator is foreseen to support the design of nano-satellites. To ensure reliable operation under harsh space conditions, (iii) appropriate redundancy concepts must be considered in hardware and software. Furthermore, we a (iv) new optical communication in nano-satellites and a new concept for a satellite bus is aspired. As already discussed at NASA and ESA for larger satellites, the computer architecture should also open up RISC-V and FPGA processor technology for nano-satellites.
CRIS-Team Scopus Importer:2025-11-21
Keywords: computer architecture; Nano-satellites; RISC-V and FPGA technology in space